THE EFFECTS OF LIFE CYCLE AND FREE CASH FLOW ON DIVIDEND OF AGRICULTURAL COMPANIES THAT LISTED IN INDONESIA STOCK EXCHANGE - Malini, Helma; Fitratama, Venu (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2020)
Company decision to give profits to their investors is based on several reasons including internal policy from the company. Therefore, this study discusses the effects of life cycle and free cash flow on dividend of agricultural companies that listed in Indonesia stock exchange. Independent variables; used are free cash flow, life cycle, firm size, leverage, assets growth, and investment opportunity set. The population in this study is Agricultural company listed on Indonesia Stock Exchange (BEI) in the period of 2015 - 2018. The sample collected using purposive sampling methods. Total of 21 companies were determined as samples. The method of analysis in this study is panel data regression with basis on fixed effect model. The result of this study indicate that the independent variables of free cashflow, life cycle, firm size, leverage, and investment opportunity set have positive impact toward dividend payout ratio while assets growth has negative impact on dividend payout ratio. The result of determination coefficient shows that the independent variables give affect 63.69% against dependent variable.Keywords: Free cash flow, Life cycle, Firm size, Leverage, Assets growth, Investment opportunity set, Dividend payout ratio, Dividend policy